Amplification of photoacoustic effect in bimodal polymer particles by self-quenching of indocyanine green - Mokrousov, Maksim D.; Novoselova, Marina; Nolan, Jackie; Harrington, Walter; Rudakovskaya, Polina; Bratashov, Daniil N.; Galanzha, Ekaterina; Fuenzalida-Werner, Juan Pablo; Yakimov, Boris P.; Nazarikov, Gleb; Drachev, Vladimir P.; Shirshin, Evgeny A.; et al. (Biomedical Optics Express, 2019)
A new type of bimodal contrast agent was made that is based on the self-quenching of indocyanine green (ICG) encapsulated in a biocompatible and biodegradable polymer shell. The increasing of a local ICG concentration that is necessary for the obtaining of self-quenching effect was achieved by freezing-induced loading and layer-by-layer assembly. As a result, an efficient photoacoustic(optoacoustic)/fluorescent contrast agent based on composite indocyanine green/polymer particles was successfully prepared and was characterized by fluorescence and photoacoustic(optoacoustic) tomography in vitro. This type of contrast agent holds good promise for clinical application owing to its high efficiency and biosafety.
CRIS-Team Scopus Importer:2023-03-08